Analisis Return On Asset Return On Equity Debt To Asset Ratio Debt To Equity Ratio Terhadap Return Saham (Study Pt. Xl Axiata Tbk Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2021) - Yoga Mudofar Bahri; Kokom Komariah; Dicky Jhoansyah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine financial performance as measured by Debt to Asset Ratio (DAR), Debt to Equity (DER), Return On Assets (ROA), Retun On Equity (ROE) on Stock Returns at PT. XL Axiata Tbk which is listed on the Indonesia Stock Exchange for the 2014-2020 period. The sampling technique was purposive sampling, obtained by companies as research samples, namely: PT. XL Axiata Tbk for the 2014-2021 period. Data collected secondary data with descriptive and associative methods of quantitative approaches. Data analysis technique correlation analysis, analysis of the coefficient of determination, multiple linear analysis, testing the research model f test and testing research research t test with data processing using SPSS 25 software. The results showed that there was a relationship between the variable debt to asset ratio, debt to equity ratio, return on assets , return on equity on stock returns of 0.519 or 51.9% includes the criteria of a strong relationship, debt to asset ratio has a positive and not significant effect on stock returns of 1.416 debt to equity ratio has a positive and insignificant effect on stock returns of 0.042 return on assets has an effect negative and insignificant effect on stock returns of -39.662 return on equity has a positive effect and no significant effect on stock returns of 15.161 Keywords: Debt to Asset Ratio, Debt to Equity Ratio, Return On Assets, Return On Equity, and Return Saham